Facile Synthesis of ZnO–Reduced Graphene Oxide Nanocomposites for NO2 Gas Sensing Applications. Issue 11 (6th March 2015) - Kumar, Nagesh; Srivastava, Arvind Kumar; Patel, Hari Shankar; Gupta, Bipin Kumar; Varma, Ghanshyam Das
Abstract: Graphene and its exotic forms have been widely recognized as exceptional materials for gas‐sensing applications because of their extraordinary electrical conductivity and large surface area to volume ratios. Herein, chemically reduced graphene oxide (rGO) and zinc oxide–reduced graphene oxide (ZrGO) nanocomposite powders have been successfully synthesized through a simple hydrolysis method followed by annealing in ambient N2 gas. The reduction of graphene oxide by hydrazine hydrate and the decoration of the graphene surface by ZnO nanoparticles have occurred during the synthesis process. The prepared samples were characterized by various microscopic techniques to explore the surface morphology and uniformity. Spectroscopic techniques were used to investigate the quality of the as‐synthesized powder samples as well as the extent of graphitization of the samples. Coil sensors with two Pt terminals and a heating element have been designed to extensively monitor the effect of temperature on the electrical and gas‐sensing properties of the rGO and ZrGO nanocomposite samples. The ZrGO nanocomposites possess better electrical and NO2 gas sensing properties than the pristine rGO. The ZrGO nanocomposite sensor exhibits a high response (ca. 32 %) for 50 ppm NO2 at relatively low temperature (50 °C). Our results suggest that the ZrGO nanocomposite material could be used to fabricate a new generation of low‐power portable NO2 sensors. Abstract : A facile route for the synthesis of zinc oxide–reduced graphene oxide nanocomposites has been achieved for NO2 gas sensing applications.